Small-Scale and Long-Term Variability in Population Dynamics of the Cockle Cerastoderma edule in a Southern North Sea Tidal Flat System - Meyer, Julia; Kröncke, Ingrid; Bartholomä, Alexander; Heckroth, Mathias; Scheiffarth, Gregor (Frontiers in Marine Science, 2021)
The cockle Cerastoderma edule is one of the most common macrofauna species in the Wadden Sea areas of the North Sea. Cockle population dynamics are influenced by various abiotic and biotic fac-tors such as temperature, food availability and inter- and intraspecific competition. Cockles play an important role in the food web of the Wadden Sea, for instance, large shellfish-eating birds, such as oystercatchers and common eiders, use the cockle Cerastoderma edule and the blue mussel Mytilus edulis as a main diet component. However, the populations of shellfish-eating bird species have been declining dramatically across the Wadden Sea since the beginning of the 21st century. While there are detailed monitoring programmes in blue mussels due to commercial interests, little information is known about the stocks and long-term dynamics of cockles in the German Wadden Sea. To fill this gap, in 2005 a local conservation society (“Der Mellumrat e. V.”) initiated a study to sample cockles at one transect per year south of the island of Mellum, which was extended by 5 more transects in 2011. In addition to the spatial analysis, we analysed the long-term variability in cockle population dynamics. Min/max autocorrelation factor analysis (MAFA) revealed a decline in cockle abundance, while no clear length trends were found. Canonical and spearman correlation analyses exposed sig-nificant correlations between cockle abundance and length and chlorophyll a, mussel bank area as well as oystercatcher and common eider populations. This study clearly shows that there is an urgent need for comprehensive time series of cockle data to analyse and explain ecological long-term changes in cockle population dynamics in relation to environmental changes and to point out how parts of the Wadden Sea food web, such as shellfish-eating birds are affected by these changes.